ANALYSIS OF PROBLEMATICS RELATED TO THE STOCK MARKET IN ALBANIA - Kristal Hykaj (European Scientific Journal, ESJ, 2015)
The stock market efficiency, the stocks prices volatility or the advanced financial analysis for the individual investment in these capital market instruments are topics that never get outdated and that come under discussions in the academic world now and again. After the fall of the dictatorship system in 1985, Albania went through a lot of economic changes as much as the other Southeastern European countries. Throughout this period, there have been some various novice efforts toward the creation of a market that will connect people who seek money with those who can provide it, or assist the economic growth by shifting the money from less to more productive activities. Despite of these incentives undertaken in the last 25 years of the post communism period, Albanian proper institutions did not manage to give birth to a well performing stock exchange. Due to the absence of an operative stock market in Albania, there arises the question about the reasons which have influenced this fact. In the following thesis, I aim to underline some of the most reasonable causes such as informality, corruption, lack of political willpower etc. that directly have affected the absence of the organized stock market. Additionally some important measures need to be taken in order that companies which fulfill the required criteria, can list themselves on a stock exchange, gaining in such a way the opportunity to raise new capital for the implementation of new projects that will expand them in the market. Currently the dominant capital market instruments in Albania are the debt instruments issued by the government, while in the stock market, only take place some banks and a few private companies. The formation of the stock exchange in Albania requires the commitment of many state mechanisms that will support the market complex economy by drawing polices that determine how beautifully the private agents identify and exploit their economic opportunities, especially the involvement of the government would give an extra encouragement and credibility to the whole process and would be a great hand in the acceleration of EU integration process. The presence of the stock market is crucial to the economic growth of emerging countries.